IMPLEMENTASI METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSA PENYAKIT AYAM BROILER - Yuli Syafitri (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstractExpert system to diagnose diseases in web-based broiler chickens was built based on the problems of society in general who are still very unfamiliar with the disease and solutions that occur in broiler chickens. Expert system (Expert System) in general is a system that seeks to adopt human knowledge to computers, so that computers can solve problems as is usually done by experts. This expert system uses the Forward Chaining technique with the Certainty Factor method. Data collection methods in the form of literature studies, observations, interviews, literature review and browsing. In the planning of the system described in the form of DAD level 0, then derived DAD level 1. This expert system in diagnosing diseases in web-based broiler chickens supports two users, namely admin and general user. Admin can enter, change and delete symptoms, input news. General users can only consult based on the symptoms experienced by their Broiler chickens and find information about Broiler chicken diseases. The purpose of this thesis is to create a health consultation service via the internet or on-line.